Determinants of Marketing Channel, Margin and Efficiency in Local Stimulants Marketing in Osun State, Nigeria - Akerele, Ezekiel Olaoluwa; Akanni, K.A.; Agbaje, E.M.; Oyebanjo, O.; Aderinto, O. (Acta Universitatis Danubius. Œconomica, 2023)
This study examined the channel and marketing efficiency of local stimulants in selected Local Government Area of Osun State, Nigeria. A total of two hundred and forty (240) respondents were sampled. Structured questionnaire was used in obtaining data from the respondents. Specifically, the study described the socio-economic characteristics of the respondents, examined the market channel for local stimulants, the marketing margin, marketing efficiency, examined the degree of market concentration for the marketers of the local stimulants and described the constraints encountered in the marketing of local stimulants in the study area. Results from the study revealed that majority (75.8%) of the respondents had at most primary school education earning at least N53,321 per month. The results showed that market channel of local stimulants have shorter chain which reduces the marketing cost. Analysis of the marketing margin of the local stimulants revealed that typical retailers earned N323.50, N274.40, N162.50, N285.65 and N33.26 per Kilogram for bitter kola, kolanut, ginger, alligator pepper and pepper respectively. The marketing efficiencies is between 2.48 and 4.62 across markets for all the stimulants. An evaluation of market concentration revealed that pepper stimulant have the highest market concentration of 2,083 while bitter kola had the least market concentration of 871 across the LGAs. High transportation (51.5%) and middlemen rip-offs (42.6%) constituted the most common challenges confronting the respondents while low demand (3.3%) was the least challenge or constraint faced by local stimulant marketers. It is therefore recommended in order to solve the problem of finance, by forming cooperatives, the marketers can have better access to finance for their businesses rather than relying substantially on money lenders with cut-throat interest rates.